(untitled) (Sciences & Technologie. C, Biotechnologies, 2011)
Ten bacterial strains were isolated from clinical samples provided by the bacteriology laboratory (Daksi, Constantine). Among the ten strains studied, eight belong to the Enterobacteriaceaeand two are among the Pseudomonadaceae. These strains were presumptively identified by their biochemical characteristics, susceptibility or resistance to antibiotics, and total nitrogen measured by the Kjeldahl method. A phylogenetic profile was produced by phenetic methods based on the calculation of genetic distances using the Neighbor Joining algorithm (NJ) and bioinformatics analysis of 16S rRNA sequences to compare the two phylogenies (phenotypic and genotypic). The analysis of topologies obtained showed that the biochemical phenotype has some limitations in bacterial identification and sequence analysis of 16S rRNA is a key tool in bacterial identification across the case.